Weight Trends and Contributing Factors among Medical Students: A Cross-Sectional Study in Kancheepuram District, Tamil Nadu - Dr.Harsavarthini.K.R,; Dr.Manju.N.V,; Dr.Sree Arthi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Obesity poses a significant health challenge worldwide, affecting various populations,including medical students. This study investigates the prevalence of obesity among medicalstudents and its correlation with lifestyle factors and academic stress. Methods: A cross-sectional study of 424 MBBS students across all four academic years collected anthropometric measurements and administered a questionnaire to assess various lifestyle factors. Statistical analysis was performed to analyze the data. Results: Among the participants, 185 students (43.6%) were classified as either overweight or obese.A higher proportion of males (55.7%) exhibited general obesity compared to females (37.8%).Students residing away from home showed a higher prevalence of obesity (52.3%). 68.4% of students frequently consumed fast food, and 55.1% regularly consumed sweets. 61.8% of students reported insufficient physical activity. A positive family history of obesity was notedin 39.2% of students, and higher alcohol intake was associated with an increased risk of obesity, with 47.6% of students who consumed alcohol being classified as overweight orobese. No significant association was found between the year of study and smoking with overweight and obesity. Conclusion: Medical students are at significant risk of obesity, increasing their susceptibility to obesity-related health complications. The study highlights the high prevalence of obesity andoverweight among medical students and identifies several modifiable risk factors contributingto this trend. Addressing these factors through targeted interventions and promoting healthier lifestyles is crucial to mitigate the risk of obesity-related health complications among this population.